Regulation of some biochemical attributes in drought-stressed cauliflower (Brassica oleracea L.) by seed pre-treatment with ascorbic acid. Issue 2 (3rd March 2016) - Latif, M.; Akram, N. A.; Ashraf, M.
ABSTRACT: Cauliflower ( Brassica oleracea L. var. botrytis ) is widely used as a vegetable in many countries; however, productivity is adversely affected in areas affected by drought. To investigate the role of exogenously applied ascorbic acid (AsA) in mitigating the negative effects of drought on cauliflower, a pot experiment was performed using two cultivars of cauliflower 'Local' and 'S-78'. Seeds of both cultivars were soaked in 75 mg l – 1, or in 150 mg l – 1 AsA, or in water (control) for 16 h. Water-deficit stress suppressed plant growth, reduced leaf chlorophyll concentrations, relative water contents (RWC), shoot and root P and K + ion concentrations, and total soluble protein concentrations, significantly. However, significant drought-induced increases were observed in relative membrane permeability (RMP), the accumulation of total phenolic compounds, leaf free proline, glycinebetaine (GB), endogenous AsA, and hydrogen peroxide concentrations, and in the activity of superoxide dismutase (SOD). Seed treatment with 75 or 150 mg l – 1 AsA resulted in lower accumulations of H2 O2, while increasing shoot and root fresh weights and dry weights, RWC, total phenolic compound, free proline, GB, and endogenous AsA concentrations, and the activities of SOD and catalase (CAT). No changes were observed in leaf chlorophyll concentrations or in peroxidase (POD) activities, RMP, shoot and root P and K + ion accumulation, or in total soluble protein concentrations under water stress or non-stress conditions following seed treatment with AsA. 'Local' had higher proline concentrations and SOD activities; however, 'S-78' had higher RWC values, GB, and AsA concentrations. Overall, a pre-sowing treatment of cauliflower seed with 75 or 150 mg l – 1 AsA improved seedling tolerance to drought stress in both cultivars, which could be attributed to AsA-induced decreases in RMP and H2 O2 concentrations, increases in the activities of CAT and SOD, increased RWC, and higher total phenolic compound, proline, GB, and AsA concentrations. The exogenous application of AsA therefore offers an effective strategy to minimise the adverse effects of drought stress on vegetable crops, including cauliflower.